2021
DOI: 10.2298/tsci191205101i
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for creating custom multiple linear regression based short term load forecasting models by using genetic algorithm optimization

Abstract: This paper presents a novel procedure for short-term load forecasting (STLF) in distribution management systems (DMS). The load is forecasted for feeders that can be of a primarily residential, commercial, industrial or combined type. Each feeder has various amounts of distributed energy resources (DER) installed, which accounts for multiple different load patterns. Hence, the DMS cannot use a single STLF model for all forecasts. The proposed procedure addresses the specificity of each particular feeder type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 38 In this paper, the main contribution is to design a high-accuracy framework based on the STLF for real-time electrical demand estimation and then validated the real-time data for the enhancement of the proposed intelligent framework. Further studies have shown in, 39 that the real-time hourly based STLF model is effectively employed in 20 zonal areas in the USA. The intelligent-based short-term forecast approach rapidly increasing in industries as well as the electrical power market because of the high system reliability and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“… 38 In this paper, the main contribution is to design a high-accuracy framework based on the STLF for real-time electrical demand estimation and then validated the real-time data for the enhancement of the proposed intelligent framework. Further studies have shown in, 39 that the real-time hourly based STLF model is effectively employed in 20 zonal areas in the USA. The intelligent-based short-term forecast approach rapidly increasing in industries as well as the electrical power market because of the high system reliability and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The framework for designing Takagi-Sugeno-Kang (TSK) fuzzy rule-based systems using GA was proposed in [12]. Paper [13] uses a GA to select the best inputs for different multiple linear regression models. A multitude of improved particle swarm optimization (PSO) algorithms are presented in variations of works [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%